2022
DOI: 10.3390/ijerph192215217
|View full text |Cite
|
Sign up to set email alerts
|

Germinated Millet (Pennisetum glaucum (L.) R. Br.) Flour Improved the Gut Function and Its Microbiota Composition in Rats Fed with High-Fat High-Fructose Diet

Abstract: Germinated millet (Pennisetum glaucum (L.) R. Br.) is a source of phenolic compounds that has potential prebiotic action. This study aims at evaluating the action of germinated pearl millet on gut function and its microbiota composition in Wistar rats fed with a high-fat high-fructose (HFHF) diet. In the first stage, lasting eight weeks, the experiment consisted of two groups: AIN-93M (n = 10) and HFHF group (n = 20). In the second stage, which lasted ten weeks, the animals of the AIN-93M group (n = 10) were k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…In line with the reported literature, we found that food intake in all groups fed with the HFF diet was lower compared to the group on the standard chow diet [ 29 ]. This could be explained by a high-energy density of the HFF diet which improves satiety and reduces food consumption [ 30 ]. Therefore, no difference in body mass between HFF and standard chow-fed animals was found.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the reported literature, we found that food intake in all groups fed with the HFF diet was lower compared to the group on the standard chow diet [ 29 ]. This could be explained by a high-energy density of the HFF diet which improves satiety and reduces food consumption [ 30 ]. Therefore, no difference in body mass between HFF and standard chow-fed animals was found.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the NCD group, the proportion of Desulfovibrio in the HFD group was significantly higher and the proportion of Pseudomonadota was significantly lower. In the HFD group, the abundance of Desufobacterota increased, which was related to more severe obesity (Theodoro et al ., 2022). Consistent with previous studies, our data showed that the relative abundance of Desufobacterota in the HFD group increased and was improved by FMHIC supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Ademais, estudos científicos in vitro e in vivo com diferentes espécies de milheto demonstraram que a germinação foi responsável por reduzir teores de compostos fitoquímicos, como o ácido fítico de maior peso molecular, que pode prejudicar a biodisponibilidade de nutrientes. Esse fato proporcionou melhora da composição da microbiota intestinal e a função intestinal em ratos (THEODORO et al, 2022), aumento da qualidade proteica in vitro (KRISHNAN; DHARMARAJ; SARITA;SINGH, 2016), da biodisponibilidade do amido in vitro (ANNOR et al, 2017), da retenção de fibras alimentares in vitro (DIAS-MARTINS et al, 2018), de vitaminas do complexo B, dos minerais cálcio, ferro e zinco (KRISHNAN; DHARMARAJ; MALLESHI, 2012), maiores efeitos antioxidantes, potencializando o efeito biológico funcional desse grão em ratos (THEODORO et al, 2021a). Segundo Mukhopadhyay e Bandyopadhyay (2003), a extrusão termoplástica reduz os fatores que podem se complexar com nutrientes, reduzindo sua biodisponibilidade e garante a segurança microbiológica do produto.…”
unclassified